Understanding potato seed degeneration, Ecuador. Project profile. - International Potato Center (International Potato Center, 2019)
The food security of Andean small-scale potato farmers is dependent on the quality of their planting materials. Potatoes are susceptible to pathogen and pest accumulation in seed tubers over successive cycles of vegetative propagation, leading to seed degeneration and falling yields. This project aims to improve the resilience of local seed systems by addressing the causes of potato seed degeneration.